Al-doped ZnO as a multifunctional nanomaterial: Structural, morphological, optical and low-temperature gas sensing properties - Aydin, Handan; Yakuphanoğlu, Fahrettin; Aydin, Cihat (Elsevier Science Sa, 2019)
In this study, zinc oxide thin films doped with Al at different atomic ratios (0.1%, 0.5%, 1%, 2%, 5%) were prepared using sol-gel spin coating method. Crystal structure, surface morphology, optical properties of the films and their response to ammonia gas were examined. XRD results showed that the ZnO thin films had a hexagonal polycrystalline structure. It was concluded from the calculation of the crystal size and lattice constant of the films that the produced samples were a nanomaterial. Scanning electron micro-scope (SEM) and atomic force microscope (AFM) images of the samples revealed that the morphology was composed of nanostructured particles and a cluster structure made of the combination of these particles. The optical band gap (E-g) of the prepared films were found within the range of 3.251 eV -3.342 eV by using the optical absorption method. Characteristics of susceptibility against ammonia gas were evaluated depending on the Al dopant. The obtained results showed that the gas response along with the structural, morphological, and optical properties of ZnO thin films changed with Al dopant. The produced thin film samples can be used as a sensor for the detection of ammonia gas in various industrial branches. (C) 2018 Elsevier B.V. All rights reserved.
Keywords: Al-doped ZnO; Structural properties; Sol-gel synthesis; Thin films; Low-temperature NH3 gas sensor